Pemberdayaan Masyarakat Dalam Proses Pengomposan Secara Aerob Di Wilayah Pesisir Kota Ternate - Sidebang, Purnama; Purwiningsih, Dwi Wahyu (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
The large volume of waste transported to TPA, requires a solution from every level of society. Ternate is a coastal city that is famous for its natural resources like fresh fish, one of which is skipjack tuna. During the process, the gills are thrown to the side of the house, water ditch, and the sea, and can pollute the environment. Fish waste (gills and rotten fish) contains nitrogen and protein elements and can be used for composting. The activity aims to make compost with the addition of Cakalang fish gills through an aerobic composting process for people living in coastal areas in Ternate City. The method is the mentoring model, namely assistance related to making compost with the addition of Cakalang fish gills through an aerobic composting process for communities in coastal areas. The targets in this activity are women, farmer groups who live in coastal areas in Togafo Village, Ternate City. The results shows that the participants were active in every activity session, both during lectures involving material, especially during demonstrations involving participants in the manufacture and use of compost. Participants said that this service activity was useful for them in processing household waste.